"World Orders Old and New", "The New Geopolitics of Central Asia and its Borderlands" and "Creating News States in Central Asia" - Editor, The (Mongolian Journal of International Affairs, 2015)
Mongolian Journal of International Affairs Vol.2 1995: 86-90